Forest Policies and Adaptation to Climate Change in Maine: Stakeholder Perceptions and Recommendations - Soucy, Alyssa; De Urioste-Stone, Sandra; Fernandez, Ivan; Weiskittel, Aaron; Rahimzadeh-Bajgiran, Parinaz; Doak, Tom (Maine Policy Review, 2021)
Socioeconomic pressures require forest management to address the impacts of climate change. However, we must ask, Are current forest policies sufficient to deal with the impacts of climate change? Here, we report on two surveys of forest stakeholders in Maine including woodlot owners and forestry professionals and discuss their perceptions of the barriers to climate change adaptation. We conclude with several policy directions including reevaluating existing policies, expanding incentivebased policies, integrating adaptation efforts into mitigation efforts, and increasing communication and outreach.
Keywords: Forest management; incentives; barriers; resilient forest systems; incentive-based policies